Effect of omega-3 supplementation on osteoarthritis: An evidence-based case report - Jessica Ferdi; Diana Sunardi (Indonesian Nutrition Association, 2024)
Background: Osteoarthritis is marked by mild inflammation, causing cartilage damage that leads to bone remodelling and potentially reduces the quality of life. Omega-3 has anti-inflammatory properties, which can help mitigate cartilage damage. Objective: This research aims to determine the role of omega-3 in relieving pain in patients with osteoarthritis. Methods: A literature search was conducted using advanced searching on three large databases: PubMed, Cochrane, and Scopus. The search used Mesh terms according to the criteria. After assessing the relevance and suitability of the literature, two articles were selected and critically evaluated based on Oxford Center for Evidence-Based Medicine. Results: Two systematic review-meta-analyses that meet the PICO and eligibility criteria were found. One of the literature sources does not demonstrate the effect of omega-3 supplementation on joint pain, while the other literature source shows the beneficial effects of omega-3 in reducing joint pain in osteoarthritis. Conclusion: Omega-3 supplementation can alleviate joint pain in individuals with osteoarthritis. Providing omega-3 may be worth considering.